Exploring Indian Heritage: The Gut-Friendly Benefits Of Curd For Stress Resilience In College Students - Chatterjee, Kaushani; Elizabeth, Gantasala; Devi, P. Vasundhara; Reddy, P. Srinivasulu (Journal of Neonatal Surgery, 2025)
Background: The gut–brain axis mediates bidirectional communication between the gastrointestinal tract and the central nervous system, influencing stress responses, emotional well-being, and gut health. Chronic stress, particularly among college students, can disrupt this axis, leading to adverse psychological and gastrointestinal outcomes. Probiotics have gained attention as psychobiotics capable of modulating stress and mental health. Curd, a traditional fermented dairy product commonly consumed in India, is a natural and affordable source of probiotics; however, its role in stress modulation remains inadequately explored. Objectives: To assess the effect of daily curd consumption on stress levels, mental well-being, gastrointestinal health, and academic performance among college students. Methods: A randomized controlled study was conducted among 100 undergraduate students aged 18–30 years. Participants were allocated into a case group (n = 50), who consumed 200 g of homemade curd daily containing Lactobacillus acidophilus and Bifidobacterium bifidum (10⁶ CFU/mL) for 8 weeks, and a control group (n = 50) with no curd intake. Stress levels, mental well-being, gastrointestinal health, and academic performance were evaluated at baseline and post-intervention using validated questionnaires: Perceived Stress Scale-10 (PSS-10), Warwick–Edinburgh Mental Well-Being Scale (WEMWBS), Digestive Health Questionnaire (DHQ), and Academic Performance Scale (APS). Statistical analysis was performed using SPSS, with p < 0.05 considered statistically significant. Results: The curd-consuming group demonstrated a significant reduction in stress levels, with severe stress decreasing from 20% to 2.5% (p < 0.001). Mental well-being scores improved significantly (p = 0.003), while gastrointestinal health showed notable improvement, with good health scores increasing from 65% to 87.5% (p = 0.039). Academic performance showed modest but significant improvement (p = 0.039). No significant changes were observed in the control group. Conclusion:Regular consumption of curd significantly reduces stress and improves mental well-being and gastrointestinal health among college students, supporting its potential role as a simple, culturally acceptable, psychobiotic dietary intervention. ..